STRATEGIC APPROACH TO MULTIFUNCTIONAL DEVELOPMENT OF AGRICULTURE AND FARMLANDS (Revista Inclusiones, 2020)
The article reveals the theoretical conceptual provisions for the formation of themultifunctional development strategy of the agricultural sector and farmlands (hereinafter - the Strategy), the innovative segment of their economic growth. The priority directions of the strategic development of agriculture were developed, taking into account the differentiation of farmlands, and four development scenarios were proposed for different types of farmlands (inertial, optimistic, innovative and harmonious) indicating the risks for each of them. The article identifies the priority direction of innovation in agriculture – the dairy cattle breeding industry, which is the driver of strategic development of both the agro-industrial complex and the economy of farmlands in general. The stages and the mechanism for managing the strategy of multifunctional development of the agriculture and farmlandswere presented. A set of basic measures for agriculturewere proposed, focused on the implementationof the main function (production) and supporting functions (social, economic, environmental, managerial), as well as breakthrough development of the agro-industrial complex, creating conditions to increase the share of small and medium-sized businesses in the rural economy, including various types of self-employment and diversification. The main target parameters of the development scenarios are calculated up to 2025 on the example ofthe Omsk Region (Siberian Federal District).